Problems and Issues of Musical Education at School in Tashkent Region - Kimsanov Okhunjon Ilkhomjonovich (Global Scientific Publishing, 2022)
the article deals with the development of professional competence of the future teacher of musical education of preschool children. The method of musical education of children as an integral part of the system of pedagogical Sciences constantly comes into connection with General and preschool pedagogy, so it is important in the development of children
Keywords: music education; teaching method; didactics; preschoolers